2018
DOI: 10.1088/2058-6272/aabedf
|View full text |Cite
|
Sign up to set email alerts
|

Generation characteristics of a metal ion plasma jet in vacuum discharge

Abstract: To improve the performance of a metal ion plasma jet in vacuum discharge, an anode-insulated cone-cylinder electrode with insulating sleeve is proposed in this paper. Discharge characteristics and generation characteristics of plasma of the electrode are investigated, effects of diameter of insulating sleeve, variety of cathode material and length of the insulating sleeve on characteristics of metal ion plasma jet are discussed. Results indicate that a directional and steady plasma jet is formed by using the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A simplified single-pulse discharge circuit, which was described in detail inour previous work [11], was used to generate the discharge and is schematically presented in Figure 1 for all μCAT structures under study. The cathode was electrically connected to the negative high voltage terminal of the discharge circuit, and the anode was grounded.…”
Section: Design Of μCat and Its Circuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified single-pulse discharge circuit, which was described in detail inour previous work [11], was used to generate the discharge and is schematically presented in Figure 1 for all μCAT structures under study. The cathode was electrically connected to the negative high voltage terminal of the discharge circuit, and the anode was grounded.…”
Section: Design Of μCat and Its Circuitrymentioning
confidence: 99%
“…The current flowing to vacuum chamber (chamber current, I chamber (t)) was determined by I chamber (t) = I C (t) − I A (t). Plasma density and directional propagation speed were measured by using an improved Langmuir probe measurement method [8][9][10][11].…”
Section: Design Of μCat and Its Circuitrymentioning
confidence: 99%
“…Actually, this is a phenomenon related to electrostatic forces, and it can occur in vacuum conditions as well as in air. Corona discharge can occur under variable air pressures [32][33][34][35], either below the standard atmospheric pressure [36], or even in vacuum conditions [37][38][39][40]. The precursor and trigger of vacuum discharges and breakdowns is the field emission [41].…”
Section: History Of Ionic Windmentioning
confidence: 99%
“…In the process of studying ejection performance of vacuum metal plasma jets, it was found that most charged particles enter the anode when it is directly grounded, which leads to a decrease in the ejection performance of a plasma jet ejected along the axis of an insulating sleeve nozzle, including plasma density and propagation velocity. In order to prevent charged particles from entering the anode, J. Tian proposed a fully insulated anode structure [23]. However, discharge difficulty increased and plasma production was reduced.…”
Section: Introductionmentioning
confidence: 99%